2021
DOI: 10.1109/tuffc.2020.3020776
|View full text |Cite
|
Sign up to set email alerts
|

Video-Capable Ultrasonic Wireless Communications Through Biological Tissues

Abstract: The use of wireless implanted medical devices (IMDs) is growing because they facilitate monitoring of patients at home and during normal activities, reduce the discomfort of patients and reduce the likelihood of infection associated with trailing wires. Currently, radiofrequency (RF) electromagnetic waves are the most commonly used method for communicating wirelessly with IMDs. However, due to the restrictions on the available bandwidth and the employable power, data rates of RF-based IMDs are limited to 267 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In [22], the authors built a proof of concept capsule device that demonstrated the feasibility of delivering gastrointestinal therapeutic drugs using ultrasound microbubble agents. In [23], ultrasonic waves were used to transmit video recordings at video-capable data rates using millimeter-sized transducers through water and ex vivo beef liver, ex vivo pork chop and in situ rabbit abdomen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [22], the authors built a proof of concept capsule device that demonstrated the feasibility of delivering gastrointestinal therapeutic drugs using ultrasound microbubble agents. In [23], ultrasonic waves were used to transmit video recordings at video-capable data rates using millimeter-sized transducers through water and ex vivo beef liver, ex vivo pork chop and in situ rabbit abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we first establish a video broadcast link through the abdominal wall of an anesthetized rabbit. We show that using the communication system presented in [23], it was possible to broadcast standard definition video obtained with an endoscopy camera using a millimeter-sized ultrasonic transducer implanted behind the abdominal wall. We then demonstrate video transmission through a saline-filled porcine intestine wrapped with bacon using mm-sized transducers.…”
Section: Introductionmentioning
confidence: 99%
“…Nonflat frequency response, severe ISI, and time variations are also present in a typical underwater acoustic communication (UWAC) channel [10]. It is demonstrated in UWAC and other related acoustic communications literature that understanding channel properties and tailoring communication methods to address particular challenges may provide significant improvements in data rates [10]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…To enable in-body ultrasound communications with a footprint small enough to fit in a small in-body device, like an endoscopy capsule, and with data rates capable of streaming video requires small transducer elements, a small processing unit and sufficient ultrasonic power. In a recent study by Bos, et al, small individual ultrasonic elements, i.e., ultrasonic microcrystals (Sonometrics, London Ontario), were used as transmit and receive transducers [9], [10]. These microcrystals are 2 mm in diameter, operate at center frequency of 1.2 MHz, are biocompatible and have low directivity.…”
mentioning
confidence: 99%
“…These microcrystals are 2 mm in diameter, operate at center frequency of 1.2 MHz, are biocompatible and have low directivity. In one of those studies, data rates of 4.4 Mbps were achieved through beef liver with quadrature amplitude modulation (QAM) and a decision feedback equalizer [10]. Bos et al used QAM and orthogonal frequency division multiplexing (OFDM) modulation to achieve data rates over 300 kbps through beef samples and over distance of 10 cm [11].…”
mentioning
confidence: 99%